Upaya Meningkatkan Prestasi Belajar Materi Peredaran Darah Pada Manusia Melalui Model Index Card Match Pada Siswa Kelas VIII SMP Negeri 1 Dukun Kabupatan Magelang - Suhartatik, Yuni (Faculty Of Education, 2022)
The aim of this research is to improve learning achievement in the material of Human Blood Circulation System on grade VIII students of SMP Negeri 1 Dukun, Magelang Regency with Index card match Model. The research method used 2 cycles of class action research. There were 32 students as the research subject. The data source of research obtained from qualitative data in the form of teacher and students' result of observation activity and quantitative in the form of students learning outcomes test data. The result of research in cycle I obtained 23 students who got individually complete score with average value of 76,5. While, the result of research in cycle II increased individually complete score from 31 students with average value of 83,25. Based on the research, learning with Index card match Model can improve learning outcomes in the material of Human Blood Circulation System on Grade VIII Students of SMP Negeri 1 Dukun Magelang Regency. The amount of improvement from Cycle I to II is 6,75.